Investigating the Benefits of Renewable Energy in Afghanistan - Mohammadi, Zaman (Journal of Natural Sciences – Kabul University, 2025)
Afghanistan, as a country with diverse natural resources, can widely benefit from renewable energies. This review-comparative article examines the advantages of renewable energy in Afghanistan, including solar, wind, hydro, and biomass energy. The article addresses challenges such as the lack of proper infrastructure, insufficient technical knowledge and skilled labor, the need for investment by the government and institutions, as well as practical solutions including the development of renewable energy infrastructure, training of specialized human resources, and investment in the renewable energy sector for implementing renewable energy projects in Afghanistan. It also provides recommendations for policymakers to maximize the use of renewable energies in the country. The findings of this article showed that utilizing these resources can contribute to environmental protection, reducing dependence on fossil fuels, providing a reliable energy source, economic development and job creation, and improving energy access in remote areas.